Italia linguistica and the European Charter for Regional or Minority Languages. (August 2014) - Cravens, Thomas D
The European Charter for Regional or Minority Languages requires member states that have ratified and signed to support the survival and use of longstanding minority languages within their borders. While the Charter offers some guidance in the selection of qualified languages, its definitions are far from rigorous and leave considerable room for arbitrary selection. Moreover, the selections are left entirely to government entities of each state. The result in the case of Italy is that a very small collection of the nation's plethora of languages has been deemed worthy of support. This article urges reconsideration of the decision-making process in light of the plurilinguistic reality of Italy and the Charter 's purpose of guaranteeing linguistic minorities the integrity of their voice.